The first principle screening and design of the high-performance organic photosensitizers based on EY2− dye in homogeneous non-noble metal photocatalytic hydrogen production system. (6th October 2021) - Lin, Chundan; Xiang, Wenli; Wang, Guochen; Yang, Zhenqing
Abstract: Photocatalytic hydrogen production, capable of dissociating water to make hydrogen using sunlight as abundant and clean energy, provides a promising solution for energy crisis. However, currently dominated metal complexes photosensitizers are based on precious and rare metal elements, which prohibits large scale applications. Herein, based on the experimental dye Eosin Y (EY 2− ), we report a series of metal-free organic dyes EY 2- 1- EY 2- 18 and present a systematic study on their ground-state geometry, electrochemistry, energy gap, reduction potential and driving force by using density functional theory (DFT) and time-dependent DFT (TDDFT). The calculated results show that compared to other dyes, the dye EY 2- 11 has a large visible light absorption range, a higher reduction potential and greater driving force, which indicates that EY 2- 11 is a promising candidate for the visible-light-driven hydrogen production. Our theoretical researches are expected to provide valuable insights for designing efficient metal-free organic photosensitizers. Graphical abstract: Image 1 Highlights: The non-noble metal photocatalytic hydrogen production system was further constructed by designing organic photosensitizer. Reasonable matching of hydrogen production system is helpful to the realization of high hydrogen production performance. EY 2- 11 has better catalytic performance by visible light, which indicates that EY 2- 11 is a promising candidate. Provide valuable insights for designing efficient organic photosensitizers.